Factors affecting abundance and primary productivity of phytoplankton in a wetland ecosystem of Bangladesh - Karim, Ehsanul; Nahiduzzaman, Md.; Nisheeth, Nazia Naheen; Bhadra, Anuradha; Mahmud, Yahia (Journal of Fisheries, 2023)
Wetlands are the most productive, economically important and hydrologically variable ecosystems. In this study, the abundance of phytoplankton and its primary productivity were evaluated in Dingapota Haor of Bangladesh. A total of 41 phytoplankton genera belong to Chlorophyceae (15), Bacillariaophyceae (14), Cyanophyceae (8) and Euglenophyceae (4) were recorded whereas Bacillariaophyceae (37.02%) was the most dominant. The highest cell density (22.71×104 cell L–1) was recorded in pre-monsoon. Diversity indices were also significantly higher in pre-monsoon. The species diversity, evenness and richness varied from 2.51–3.79, 0.57–0.90 and 4.65–7.50 respectively. Difference in phytoplankton assemblage with an overall average dissimilarity value of 52.56 % was recorded. Cyclotella (3.60%), Bacillaria (3.13%), Volvox (2.95%), Spirulina (2.92%) and Euglena (2.88%) were the five most contributory species to the seasonal variation. Gross Primary Production, Net Primary Production and Community Respiration values ranged from 0.90–2.49, 0.68–1.60 and 0.35–0.89 mgCm–3day–1 respectively. Alkalinity and Chl-a showed significant positive correlation with GPP, NPP and CR. Pre-monsoon was the most productive phase whereas the monsoon season was the least productive. The current study produced valuable baseline data that will aid in the formulation of wetland conservation and management strategies.